Hemispheric-wide climate response to regional COVID-19-related aerosol emission reductions: the prominent role of atmospheric circulation adjustments - N. L. S. Fahrenbach; M. A. Bollasina (Atmospheric Chemistry and Physics, 2023)
The national and global restrictions in response to the COVID-19 pandemic led to a sudden, albeit temporary, emission reduction of many greenhouse gases (GHGs) and anthropogenic aerosols, whose near-term climate impact were previously found to be negligible when focusing on global- and/or annual-mean scales. Our study aims to investigate the monthly scale coupled climate-and-circulation response to regional, COVID-19-related aerosol emission reductions, using the output from 10 Earth system models participating in the Covid model intercomparison project (CovidMIP). We focus on January–February and March–May 2020, which represent the seasons of largest emission changes in sulfate (SO2) and black carbon (BC). During January–February (JF), a marked decrease in aerosol emissions over eastern China, the main emission region, resulted in a lower aerosol burden, leading to an increase in surface downwelling radiation and ensuing surface warming. Regional sea-level pressure and circulation adjustments drive a precipitation increase over the Maritime Continent, embedded in a negative Pacific Decadal Oscillation (PDO)- and/or El Niño–Southern Oscillation (ENSO)-like response over the Pacific, in turn associated with a northwestward displacement and zonal shrinking of the Indo-Pacific Walker cell. Remote climate anomalies across the Northern Hemisphere, including a weakening of the Siberian High and Aleutian Low, as well as anomalous temperature patterns in the northern mid-latitudes, arise primarily as a result of stationary Rossby wave trains generated over East Asia. The anomalous climate pattern and driving dynamical mechanism reverse polarity between JF and MAM (March–May) 2020, which is shown to be consistent with an underlying shift of the dominant region of SO2 emission reduction from eastern China in JF to India in MAM. Our findings highlight the prominent role of large-scale dynamical adjustments in generating a hemispheric-wide aerosol climate imprint even on short timescales, which are largely consistent with longer-term (decadal) trends. Furthermore, our analysis shows the sensitivity of the climate response to the geographical location of the aerosol emission region, even after relatively small, but abrupt, emission changes. Scientific advances in understanding the climate impact of regional aerosol perturbations, especially the rapidly evolving emissions over China and India, are critically needed to reduce current uncertainties in near-future climate projections and to develop scientifically informed hazard mitigation and adaptation policies.